Influence of ingesting a carbohydrate-electrolyte solution on endurance capacity during intermittent, high-intensity shuttle running - Nicholas, C. W.; Williams, C.; Lakomy, H. K.; Phillips, G.; Nowitz, A. (Journal of Sports Sciences, 1995)
The aim of this study was to examine the effects of ingesting a carbohydrate-electrolyte solution on endurance capacity during a prolonged intermittent, high-intensity shuttle running test (PIHSRT). Nine trained male games players performed two exercise trials, 7 days apart. On each occasion, they completed 75 min exercise, comprising of five 15-min periods of intermittent running, consisting of sprinting, interspersed with periods of jogging and walking (Part A), followed by intermittent running to fatigue (Part B). The subjects were randomly allocated either a 6.9% carbohydrate-electrolyte solution (CHO) or a non-carbohydrate placebo (CON) immediately prior to exercise (5 ml kg-1 body mass) and every 15 min thereafter (2 ml kg-1 body mass). Venous blood samples were obtained at rest, during and after each PIHSRT for the determination of glucose, lactate, plasma free fatty acid, glycerol, ammonia, and serum insulin and electrolyte concentrations. During Part B, the subjects were able to continue running longer when fed CHO (CHO = 8.9 +/- 1.5 min vs CON = 6.7 +/- 1.0 min; P < 0.05) (mean +/- S.E.M.). These results show that drinking a carbohydrate-electrolyte solution improves endurance running capacity during prolonged intermittent exercise.